Evaluation of a manual to guide antibiotic therapy in patients with dialytic chronic kidney disease in medicine graduation (Research, Society and Development, 2023)
In the current context, it is known that the prevalence of chronic kidney disease (CKD) is increasing worldwide, which also raises the costs for the adequate treatment of these patients. Given this scenario, acute infectious processes represent an important cause of morbidity and mortality in patients with CKD. The use of digital technology appears as a potential tool to help guide the best antibiotic treatment for the infection at each site would improve the treatment of these individuals. With reviews of updated national and international sources, a mobile manual was developed, easy and practical to use, to help teach about the most appropriate individualized treatment options, taking into account clinical, laboratory and social characteristics of patients with chronic kidney disease. The manual was evaluated by 40 contributors, mean age 24.2 years, female being 56.4%. the material in the manual was considered adequate to be used in consultations for the choice of antibiotics in patients with chronic kidney disease in 92.5% of the answers, being also able to contribute to a good care delivery to these patients, representing 90% of the results. the manual was classified with 89.7% of the answers for a clear, simple and objective presentation, and a percentage of 90% in relation to scientifically adequate for the medical field. It was concluded that the manual is a support for health professionals, which has shown good acceptance, in view of the practicality of use, satisfaction and simple and quick use for teaching students and health professionals.